Supervisi Akademik Untuk Meningkatkan Kulitas Kinerja Guru di Madrasah Tsanawiyah Negeri (MTsN) Karo - Inom Nasution; Yuni Syafriani; Suci Ramadhani; Dawi Nurjannahi; Amar Khairi Ahmad; Imam Amir Musthofa; Accep Noor Akbar Sambo (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The author chose the title Academic Supervision To Improve Teacher Performance at Madrasah Tsanawiyah State (MTsN) Karo, the first goal is to find out the planning of the academic supervision program at Madrasah Tsanawiyah State (MTsN) Karo, the second is to know the implementation of the academic supervision program at Madrasah Tsanawiyah State (MTsN) Karo, and the last is to know the evaluation of the academic supervision program at Madrasah Tsanawiyah State (MTsN) Karo. This study uses a qualitative descriptive analytic method in which the results of observations, interviews, document analysis, field notes are obtained and are not made in the form of numbers. This research was conducted at Madrasah Tsanawiyah State (MTsN) Karo directly conducted an interview with the Head of the Madrasah. From the results of the study, it was found that 1) the implementation of supervision carried out by the Head of the Madrasah Tsanawiyah State (MTsN) Karo was carried out once a month and the implementation was carried out in stages, first holding a meeting, second checking the completeness of learning tools, third class visits and finally any follow-up or evaluation after supervision is carried out, 2) the implementation of supervision at Madrasah Tsanawiyah State (MTsN) Karo using class visit techniques, 3) Evaluation carried out by the Head of Madrasah at MTsN Karo to improve teacher performance is through learning assessment by monitoring students' test results and it is hoped that through In this evaluation, teachers further improve their perform.